2018
DOI: 10.1111/febs.14687
|View full text |Cite
|
Sign up to set email alerts
|

2‐Deoxy‐D‐glucose has distinct and cell line‐specific effects on the survival of different cancer cells upon antitumor drug treatment

Abstract: The dependence of tumors on glycolysis for ATP generation offers a rationale for therapeutic strategies aimed at selective inhibition of the glycolytic pathway. Analysis of tumor cell responses to anticancer drugs revealed that inhibition of glycolysis by 2‐deoxy‐D‐glucose (2‐DG) generally augmented the apoptotic response; however, in HCT116 human colon carcinoma cells, apoptosis was suppressed. A comparison of neuroblastoma SK‐N‐BE(2) and HCT116 cells revealed, that in contrast to HCT116, in SK‐N‐BE(2) cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 21 publications
(23 reference statements)
1
22
0
1
Order By: Relevance
“…It has been reported that 2-DG decreases the migration of triple-negative breast cancer cells, supporting a link between metabolic dysfunction and decreased migration (32). A previous study demonstrated that 2-DG attenuates ATP production, and also inhibits mitochondrial bioenergetics (33). 2-DG combined with other antitumor drugs, such as metformin, propranolol or docetaxel, effectively prevents cell proliferation and induces apoptosis in prostate cancer cells and other solid tumors, for example NSCLC and adenoid-cystic carcinoma (34,35).…”
Section: Discussionmentioning
confidence: 82%
“…It has been reported that 2-DG decreases the migration of triple-negative breast cancer cells, supporting a link between metabolic dysfunction and decreased migration (32). A previous study demonstrated that 2-DG attenuates ATP production, and also inhibits mitochondrial bioenergetics (33). 2-DG combined with other antitumor drugs, such as metformin, propranolol or docetaxel, effectively prevents cell proliferation and induces apoptosis in prostate cancer cells and other solid tumors, for example NSCLC and adenoid-cystic carcinoma (34,35).…”
Section: Discussionmentioning
confidence: 82%
“…2-DG additively enhanced apoptosis in CPT-treated SK-N-BE(2) which was diminished by ER-stress inhibition or autophagy induction by rapamycin. In contrast, 2-DG rescued HCT116 from CPT-induced apoptosis which was even more visible after the addition of rapamycin and attenuated by ERstress inhibition [80].…”
Section: -Deoxy-d-glucosementioning
confidence: 85%
“…This widely studied metabolic shift, often considered as one of cancer hallmarks, is called Warburg effect. Energetic imbalance with alerted ATP:ADP ratio leads to changes in autophagy and cell death which may potentialize antineoplastic efficacy of chemotherapeutics [80].…”
Section: -Deoxy-d-glucosementioning
confidence: 99%
“…However, clinical studies on the application 2-DG in cancers have reported that 2-DG administration induces several side effects, such as fatigue and dizziness, among others (22,23). Additionally, the effective concentration of 2-DG on cancer cells has been found to vary across different cancer cells (11,19,24,25). The underlying mechanism of such differences is poorly understood and the administration of high concentrations of 2-DG increases the risk of side effects.…”
Section: Discussionmentioning
confidence: 99%